Synthesis, characterization, and electrical, electrochemical and gas sensing properties of a novel ball-type four t-butylcalix[4]arene bridged binuclear zinc(II) phthalocyanine - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2006)
1,3 dimethoxy-4-t-butylcalix[4]arene has been used to synthesize a novel ball-type dimeric zinc(II) phthalocyanine, [Zn2Pc2(tbca)4] that exhibits mixed-valence behaviour and non-Arrhenius type dependence of conductivity.
Keywords: SANDWICH DILUTETIUM TETRAPHTHALOCYANINE; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE